PATTERNS OF TRANSCRANIAL DOPPLER FLOW VELOCITIES AND CAROTID INTIMA MEDIA THICKNESS (CIMT) IN JAVANESE ISCHEMIC STROKE - Danuaji, Rivan; Subandi, Subandi; Apriyanto, Arif; Dewi, Endang Kusuma; Suroto, Suroto; Mirawati, Diah Kurnia; Budianto, Pepi; Hambarsari, Yetty; Hamidi, Baarid Lukman; Prabaningtyas, Hanindya Riani; Sulistyani, Sulistyani (Biomedika, 2020)
ABSTRACTIntracranial atherosclerosis is the most common cause of stroke in Asia including Indonesia. Transcranial Doppler (TCD) is a noninvasive tool which able to detect intracranial atherosclerosis. The purpose of this study was to determine the pattern of TCD waves in Javanese ischemic stroke patients and Carotid Intima Media Thickness (CIMT), and its correlation to demographic data. This is a cross-sectional study was conducted at Hospital X Surakarta. All Javanese ischemic stroke treated in stroke unit were examine for flow velocity using TCD and CIMT using ultrasound. Chi square was used to analyzes the relationship between age, gender, stroke type and the thickness of CIMT.  A total of 43 ischemic stroke patients were examined for TCD, consisting of 30 (69.77%) men and 13 (30,23%) women. The results showed that 31 (72.09%) had intracranial abnormalities in the form of stenosis or occlusion on MCA (23.26%), ACA (4.65%), PCA (4.65%), vertebral arteries (6.98 %) and other locations (32.56%). Thickening of CIMT was obtained as much as 22 (51,16%) of the patients. Age was a factor associated with CIMT thickening with (P: 0.041), while gender and type of stroke did not (P>0,05)). To sum up Intracranial flow velocity abnormalities often occur in Javanese ischemic stroke patients, while CIMT thickening is not associated with ischemic stroke pathologyKeywords: TCD, Stroke Ischemic, Flow Velocity, CIMT, JavaneseABSTRAKAterosklerosis intrakranial adalah penyebab paling umum dari stroke di Asia termasuk Indonesia. Transcranial Doppler (TCD) adalah alat noninvasif yang mampu mendeteksi aterosklerosis intrakranial. Tujuan dari penelitian ini untuk mengetahui pola gelombang TCD pada pasien stroke iskemik suku Jawa dan Carotid Intima Media Thickness (CIMT), dan korelasinya dengan data demografi. Penelitian cross-sectional ini dilakukan di Rumah Sakit X Surakarta. Semua stroke iskemik suku Jawa yang dirawat di unit stroke diperiksa untuk kecepatan aliran menggunakan TCD dan CIMT menggunakan ultrasound. Chi square digunakan untuk menganalisis hubungan antara usia, jenis kelamin, jenis stroke dan ketebalan CIMT. Sebanyak 43 pasien stroke iskemik diperiksa untuk TCD, terdiri dari 30 (69,77%) pria dan 13 (30,23%) wanita. Hasil penelitian menunjukkan bahwa 31 (72,09%) memiliki kelainan intrakranial dalam bentuk stenosis atau oklusi pada MCA (23,26%), ACA (4,65%), PCA (4,65%), arteri vertebral (6,98%) dan lokasi lain (32,56%). Penebalan CIMT diperoleh sebanyak 22 (51,16%) dari pasien. Usia adalah faktor yang terkait dengan penebalan CIMT dengan (p= 0,041), sedangkan jenis kelamin dan jenis stroke tidak (p> 0,05), sehingga ditarik kesimpulan bahwa kelainan kecepatan aliran intrakranial sering terjadi pada pasien stroke iskemik Jawa, sedangkan penebalan CIMT tidak berhubungan dengan patologi stroke iskemik.Kata Kunci: TCD, Stroke Iskemik, Flow Velocity, CIMT, Suku Jawa